A Simulation Model for the Demographic Transition in Germany: Data Requirements, Model Structure and Calibration - Sabine Jokisch; Gitte Halder; Hans Fehr (University of Würzburg, Department of Economics, 2004)
All countries in the European Union stand at the fore of a phenomenal demographic transition. Especially Germany will realize an enormous aging of its population. The reasons for this development are twofold: On the one hand, the number of elderly will more than double over the coming decades. On the other hand, since fertility rates are projected to stay at a low level, the number of workers available to pay the elderly their government-guaranteed pension and health care benefits will decline. Due to very generous social security systems this aging process is expected to put enormous pressure on future government expenses. To address the consequences of population aging in Germany, this paper develops a dynamic, intergenerational demographic life-cycle model. The model features immigration, age-specific fertility, life span extension and life span uncertainty. Cohorts within the model differ in their human capital profiles and leave bequests arising from incomplete annuitization. We also incorporate the German pension, health care and long-term care system. After introducing the theoretical model, we simulate the transition path including reforms of the pension system imposed by the so called "Riester" reform and keeping current immigration constant. The results are presented for the case of a closed and a small open economy.
Keywords: J11; H55; D58; 330; Demographic transition; overlapping generations (OLG); computable general equilibrium models (CGE); Alternde Bevölkerung; Bevölkerungsökonomie; Overlapping Generations; Allgemeines Gleichgewicht; Deutschland